2022
DOI: 10.1021/acs.est.2c02089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Compound-Specific Fatty Acid δ13C and δ2H Values to Track Fish Mobility in a Small Sub-alpine Catchment

Abstract: Methods for identifying origin, movement, and foraging areas of animals are essential for understanding ecosystem connectivity, nutrient flows, and other ecological processes. Telemetric methods can provide detailed spatial coverage but are limited to a minimum body size of specimen for tagging. In recent years, stable isotopes have been increasingly used to track animal migration by linking landscape isotope patterns into movement (isoscapes). However, compared to telemetric methods, the spatial resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Deuterium is fractioned similarly to 13 C but within the water cycle through different processes such as condensation across different latitudes and evaporation ( 54 ). 2 H isotope composition has been used to track migration using precipitation gradients across geographical regions ( 55 ), though this method is rapidly advancing to assess food sources and metabolism of PUFA ( 56 ). 2 H values may have a larger isotopic separation between diet sources because of larger relative mass differences ( 57 ), and could be use to study PUFA metabolism in humans in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Deuterium is fractioned similarly to 13 C but within the water cycle through different processes such as condensation across different latitudes and evaporation ( 54 ). 2 H isotope composition has been used to track migration using precipitation gradients across geographical regions ( 55 ), though this method is rapidly advancing to assess food sources and metabolism of PUFA ( 56 ). 2 H values may have a larger isotopic separation between diet sources because of larger relative mass differences ( 57 ), and could be use to study PUFA metabolism in humans in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…In different study settings, we recently demonstrated that carbon and hydrogen isotope values of fatty acid generally show independent patterns [ 21 , [23] , [24] , [25] , [26] , [27] ]; however, these patterns might influence each other and exhibit negative kinetic inhibition in metabolic processes if one isotope is artificially enriched in an experimental setup [21] . So far, our findings also indicate that δ 13 C values of FA are conservative, meaning they show fewer inter-species and metabolic (i.e., ecophysiological) dynamics within a specific spatial and temporal area and have a high potential for particular site tracing of the origin of a sample.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, δ 2 H values of FA are highly sensitive to environmental and physiological changes. They can exhibit a comparatively extensive range of δ -values; thus, H isotopes are preferable when investigating metabolic and ecophysiological processes [ 21 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation